Design a Reconfigurable Microwave Combline Filter - Rosli, Muhammad Solihin (2017)
Radio frequency (RF) and microwave filter can be designed and fabricated using transmission lines instead of lumped elements. Besides, it is easier to implement RF and microwave filter depending on the type of transmission lines. The microstrip transmission line can be fabricated using Printed Circuit Board (PCB). In this project, a varactor-tuned microwave combline filter was designed to replace the conventional filter bank due to its compactness for modern communication devices. A varactor was chosen as tuning element because its capacitances can be manipulated when biasing with different voltage level. A second order combline filter, which consists of an array of two resonators and two impedance matching stubs was designed in Advance Design System (ADS). The schematic circuit simulation together with the momentum simulation has been performed. The result shows that there are two resonances within the passband as the design is based on second order combline filter. The insertion loss is less than 2 dB and the return loss is less than 15 dB as desired. The layout of the microstrip is generated in gerber file and then sent for fabrication. The circuit prototype of the second order combline filter has been fabricated. The fabricated circuit was then measured using network analyzer and the data were measured. Due to the time constraint, however, the loaded capacitors are not yet to be replaced by the varactors with the biasing circuits. This is to be recommended for the future work.